UPAYA PENCEGAHAN TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH KEPALA DESADI KECAMATAN RETEH KABUPATEN INDRAGIRI HILIR (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This study aims to determine the efforts to prevent corruption in the Reteh sub-district, Indragirihilir district. Eradication of corruption does not only through law enforcement (repressive) but preventive measures should be prioritized. The emergence of criminal acts of corruption as regulated in Law No. 20 of 2001 concerning the Prevention of corruption, the village government is expected to do as much as possible to prevent corruption.The type of research used in writing this law is sociological legal research. Meanwhile, if viewed from the nature of this research is descriptive.This research was conducted in Reteh sub-district, Indragiri downstream district. The results obtained in terms of efforts to prevent corruption in the reteh sub-district, Indragiri downstream district, are the village government implementing efforts in the form of transparency and inviting the community to participate in building villages. about community participation in preventing corruption and the lack of role of the village consultative body (BPD)Keywords: Implementation of Restitution, Child Victims, Sexual Violence